The effect of adding zirconium dioxide nanoparticle to acrylic denture base on porosity and candida albicans adhesion - Angeline Antony; Haryo Mustiko Dipoyono; Titik Ismiyati (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Acrylic resin is the most common fabricated material for denture bases. ZrO2 nanoparticles can be used as filler to strengthen the physical properties and inhibit the adhesion of acrylic resins. This study aimed to examine the growth of Candida albicans and porosity in reinforced acrylic resin with Zirconium Dioxide (ZrO2) nanoparticles at 2.5% and 5% a concentration targeted for denture bases application. A laboratory experiment study included twenty-seven disc-shaped samples which were divided into three groups: group I acrylic resin without ZrO2 nanoparticles (control), group II acrylic resin with 2.5% ZrO2 nanoparticles, and group III with 5% ZrO2 nanoparticle acrylic resin. Samples were collected by heat polymerization while porosity observations were done using primo zeizs starr (Nikon YS100) microscope at 100x magnification. Dilution test was implemented to assess Candida albican growth. One-way ANOVA and Post Hoc LSD test statistical analysis were performed to evaluate the data (p<0.05). The results indicated that the mean porosity values in the control group of 2.5% and 5% were 37.4 ± 3.5, 15.8 ± 3.3, 8.0 ± 2.0 respectively while the attachment of C. albicans was 0.832 ± 0.083, 0.536 ± 0.098, 0.218 ± 0.083. One-way ANOVA confirmed a significant effect (p<0.05). Similarly, Post Hoc LSD test reported significant difference (p<0.05). The results showed that acrylic resin reinforced with ZrO2 nanoparticles for heat-polymerized denture base effectively reduced porosity and C. albicans adhesion. Five percent of ZrO2 nanoparticle concentration presented greater porosity reduction compared to 2.5% ZrO2 and non-reinforced acrylic resin. Acrylic resin reinforced with ZrO2 nanoparticles in 2.5% and 5% concentration is fungistatic.